2008
DOI: 10.1152/ajpheart.00903.2007
|View full text |Cite
|
Sign up to set email alerts
|

Transient receptor potential melastatin 6 and 7 channels, magnesium transport, and vascular biology: implications in hypertension

Abstract: Magnesium, an essential intracellular cation, is critically involved in many biochemical reactions involved in the regulation of vascular tone and integrity. Decreased magnesium concentration has been implicated in altered vascular reactivity, endothelial dysfunction, vascular inflammation, and structural remodeling, processes important in vascular changes and target organ damage associated with hypertension. Until recently, very little was known about mechanisms regulating cellular magnesium homeostasis, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
94
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(103 citation statements)
references
References 244 publications
5
94
0
1
Order By: Relevance
“…These comments refer to rapidly growing renal epithelial cells; some cell types, particularly neural and lymphocytic established and nonestablished, are more resilient to Mg 2ϩ deficiency. These may be more conducive to long-term studies (148,151,172).…”
Section: Strategy For Identifying Novel Mg 2؉ Transportersmentioning
confidence: 99%
See 1 more Smart Citation
“…These comments refer to rapidly growing renal epithelial cells; some cell types, particularly neural and lymphocytic established and nonestablished, are more resilient to Mg 2ϩ deficiency. These may be more conducive to long-term studies (148,151,172).…”
Section: Strategy For Identifying Novel Mg 2؉ Transportersmentioning
confidence: 99%
“…Mg 2ϩ is required for the catalytic activity of numerous metalloenzymes and can also serve a purely structural role by stabilizing the conformation of certain Mg 2ϩ -and Ca 2ϩ -dependent domains, such as Ca 2ϩ -binding proteins and transcriptional regulatory proteins. Deficiency of this essential metal has been implicated in many diseases, ranging from hypertension, migraines, and asthma to osteoporosis and other bone disorders (119,151,172). Intracellular free Mg 2ϩ concentration is on the order of 0.5 mM, which is 1-2% of the total cellular Mg 2ϩ (21,109).…”
mentioning
confidence: 99%
“…Mg 2ϩ deficiency results in small cell size and cell cycle arrest (11), as well as accelerated cell senescence (12), and intracellular Mg 2ϩ levels modulate the activity of many ion channels (13)(14)(15)(16)(17)(18). In whole animals, hypomagnesemia results in hypocalcemia (19,20), and Mg 2ϩ deficiency has been correlated to hypertension (21,22).…”
Section: Magnesium (Mgmentioning
confidence: 99%
“…Mg 2ϩ deficiency results in small cell size and cell cycle arrest (11), as well as accelerated cell senescence (12), and intracellular Mg 2ϩ levels modulate the activity of many ion channels (13-18). In whole animals, hypomagnesemia results in hypocalcemia (19,20), and Mg 2ϩ deficiency has been correlated to hypertension (21,22 (42)(43)(44)46), has raised interest in putative Mg 2ϩ channels. TRPM6 mutations have been linked to the human genetic disease familial hypomagnesemia with secondary hypocalcemia (47,48).…”
mentioning
confidence: 99%
“…Other aspects of TRPM channels are addressed in a number of excellent review articles. 7,12,[57][58][59][60][61][62][63][64] A few years ago, two independent groups showed that loss-of-function mutations in the human TRPM6 gene are the molecular cause of HSH. 10,56 HSH is an autosomal recessive disease that manifests in early infancy with generalized convulsions or symptoms of increased neuromuscular excitability including muscle spasms and tet-any.…”
Section: Role Of Trpm6 Channels In Renal Magnesium Homeostasismentioning
confidence: 99%